2019
DOI: 10.3390/ani9040140
|View full text |Cite
|
Sign up to set email alerts
|

Meat Quality and Sensory Traits of Finisher Broiler Chickens Fed with Black Soldier Fly (Hermetia Illucens L.) Larvae Fat as Alternative Fat Source

Abstract: At present, there is limited knowledge about the possible utilization of the fat fraction derived from Hermetia illucens (HI) larvae processing. The objective of the present study was to evaluate the replacement of soybean oil with HI larvae fat in broiler finisher diet, on the quality and sensory traits of their meat. At 21 days of age, 120 male broiler chickens were randomly allocated to three experimental groups (5 replicates and 8 birds/pen): a basal control diet (C), and two groups in which either 50% or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
95
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(131 citation statements)
references
References 43 publications
15
95
5
Order By: Relevance
“…Although the high composition of the PUFA is more valuable for the chicken meat quality, the SFA is less vulnerable to lipid peroxidation than the USFA and TBARS inhibition of SFA was greater than that of USFA [24,25]. On the contrary to our result, Cullere et al [22] observed that the result of TBARS did not show a significant difference by the inclusion of BSFLO in breast meat.…”
Section: A-ccontrasting
confidence: 99%
See 3 more Smart Citations
“…Although the high composition of the PUFA is more valuable for the chicken meat quality, the SFA is less vulnerable to lipid peroxidation than the USFA and TBARS inhibition of SFA was greater than that of USFA [24,25]. On the contrary to our result, Cullere et al [22] observed that the result of TBARS did not show a significant difference by the inclusion of BSFLO in breast meat.…”
Section: A-ccontrasting
confidence: 99%
“…However, the TBARS value of the control group was significantly higher (p < 0.001) than in other groups on d 0 ( Table 7). Even though the FA profile of the leg meat was only measured in the present study, the previous studies reported that the replacement of BSFLO in the broiler diet changed the FA profile of both breast meat and leg meat and the composition of SFA was also increased [6,22]. Although the high composition of the PUFA is more valuable for the chicken meat quality, the SFA is less vulnerable to lipid peroxidation than the USFA and TBARS inhibition of SFA was greater than that of USFA [24,25].…”
Section: A-cmentioning
confidence: 78%
See 2 more Smart Citations
“…Based on the functionality of medium-chain fatty acids鈥搑ich insect oils being antimicrobials and modifying body fatty acid composition, it is postulated that dietary BSFL oil could improve growth performance and gut health, alter the fatty acid composition of abdominal fat pads, and enhance meat quality in broiler chickens. It has been reported that dietary fat sources increased meat quality in broiler chickens ( Zeitz et al., 2015 , Khatun et al., 2018 , Cullere et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%